The effects of laser assisted hatching on pregnancy rates - Alireza Ghannadi; Marjaneh Kazerooni; Fatemeh Jamalzadeh; Sahar Amiri; Parifar Rostami; Forouzan Absalan (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: For infertile women aged over 35 years, failure of the ZP (zona pellucida) to rupture is believed to be associated with a decreased implantation rate in in vitro fertilization (IVF) or intra cytoplasmic sperm injection (ICSI).Objective: In this research, laser assisted hatching (LAH) was offered to patients with advanced maternal age to evaluate a possible benefit.Materials and Methods: Nine hundred thirty two cycles of IVF/ICSI in females were analyzed. Women included in this study were allocated in 4 groups. In group I and II, embryos were cultured and transferred with and without LAH in women aged ≤35, whereas embryos of group III and IV were examined with and without LAH in women aged ≥ 35. Laser manipulations were performed using a suturn-Tm3 system using 2-3 pulses of 0.8 millisecond with 400 voltage duration. The size of the hole made in the zona was measured to be 5-10 μm, depending on the zona thickness of each individual embryo.Results: The performance of LAH significantly increased clinical pregnancy rates in all patients. In group I and II, the chemical (50.99% and 31.61% respectively), clinical (50% and 30.69% respectively) and multiple pregnancies (22.27% and 5.94% respectively) significantly differ between these groups. In the patients with advanced female age ≥35 the performance of LAH significantly increased chemical (30.12%) and clinical pregnancy (27.71%) rates compared to whom without LAH (18.96% and 16.37% respectively).Conclusion: Our data demonstrate in the patients who were less than 35 years old, multiple pregnancy rates were significantly increased compared to other groups who aged over 35 years old. In addition benefit of LAH in improving pregnancy rates after IVF or ICSI in women of advanced age (≥35) was shown